The effect of nitrogen and sulphur on the nutrient use efficiency, yield and quality of canola (Brassica napus L.) grown in the Western Cape - Ngezimana, Wonder (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--Stellenbosch University, 2012.